2013
DOI: 10.1161/circresaha.111.300179
|View full text |Cite
|
Sign up to set email alerts
|

De-SUMOylation Enzyme of Sentrin/SUMO-Specific Protease 2 Regulates Disturbed Flow–Induced SUMOylation of ERK5 and p53 that Leads to Endothelial Dysfunction and Atherosclerosis

Abstract: Rationale Disturbed flow induces pro-inflammatory and apoptotic responses in endothelial cells (ECs), causing them to become dysfunctional and subsequently pro-atherogenic. Objective Although a possible link between SUMOylation of p53 and ERK5 detected during endothelial apoptosis and inflammation has been suggested, the mechanistic insights, especially under the pro-atherogenic flow condition, remain largely unknown. Methods and Results SUMOylation of p53 and ERK5 was induced by disturbed flow but not by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
122
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 92 publications
(127 citation statements)
references
References 34 publications
2
122
3
Order By: Relevance
“…Previously, we found that d-flow induced SUMOylation of p53 (3) and ERK5 (12), leading to EC apoptosis and inflammation, respectively. Reduced expression of sentrin/SUMO-specific protease 2 (SENP2) increased p53 and ERK5 SUMOylation, hence accelerating EC dysfunction, inflammation, and consequently, atherosclerotic plaque formation in mice (11). Although these results might suggest SENP2 expression being downregulated by d-flow, we failed to detect such a change in ECs exposed to d-flow in vitro (11).…”
Section: Introductionmentioning
confidence: 69%
See 4 more Smart Citations
“…Previously, we found that d-flow induced SUMOylation of p53 (3) and ERK5 (12), leading to EC apoptosis and inflammation, respectively. Reduced expression of sentrin/SUMO-specific protease 2 (SENP2) increased p53 and ERK5 SUMOylation, hence accelerating EC dysfunction, inflammation, and consequently, atherosclerotic plaque formation in mice (11). Although these results might suggest SENP2 expression being downregulated by d-flow, we failed to detect such a change in ECs exposed to d-flow in vitro (11).…”
Section: Introductionmentioning
confidence: 69%
“…Because we have reported that d-flow SUMOylates p53 and ERK5 (11) and because both Ad-DN-p90RSK and a specific p90RSK kinase inhibitor, FMK-MEA, completely inhibit d-flowinduced p90RSK activation (refs. 13, 14, and Supplemental Figure 2B), p90RSK may play a role in p53 and ERK5 SUMOylation by Disturbed blood flow (d-flow) causes endothelial cell (EC) dysfunction, leading to atherosclerotic plaque formation.…”
Section: P90rsk Activation By D-flow Induces Ec Apoptosis and Inflammmentioning
confidence: 99%
See 3 more Smart Citations